Distinct mechanisms regulating mechanical force-induced Ca2+ signals at the plasma membrane and the ER in human MSCs - Kim, Tae-Jin; Joo, Chirlmin; Seong, Jihye; Vafabakhsh, Reza; Botvinick, Elliot L.; Berns, Michael W.; Palmer, Amy E.; Wang, Ning; Ha, Taekjip; Jakobsson, Eric; Sun, Jie; Wang, Yingxiao (ELIFE SCIENCES PUBLICATIONS LTD, 2015)
It is unclear that how subcellular organelles respond to external mechanical stimuli. Here, we investigated the molecular mechanisms by which mechanical force regulates Ca2+ signaling at endoplasmic reticulum (ER) in human mesenchymal stem cells. Without extracellular Ca2+, ER Ca2+ release is the source of intracellular Ca2+ oscillations induced by laser- tweezer- traction at the plasma membrane, providing a model to study how mechanical stimuli can be transmitted deep inside the cell body. This ER Ca2+ release upon mechanical stimulation is mediated not only by the mechanical support of cytoskeleton and actomyosin contractility, but also by mechanosensitive Ca2+ permeable channels on the plasma membrane, specifically TRPM7. However, Ca2+ influx at the plasma membrane via mechanosensitive Ca2+ permeable channels is only mediated by the passive cytoskeletal structure but not active actomyosin contractility. Thus, active actomyosin contractility is essential for the response of ER to the external mechanical stimuli, distinct from the mechanical regulation at the plasma membrane.
Keywords: INTRACELLULAR CALCIUM-RELEASE; MECHANOSENSITIVE ION CHANNELS; MESENCHYMAL STEM-CELLS; SMOOTH-MUSCLE-CELLS; LIGHT-CHAIN KINASE; T-LYMPHOMA CELLS; NITRIC-OXIDE; MOLECULAR-BASIS; IP3 RECEPTORS; LIVING CELLS